CHILD syndrome combined linear porokeratosis in a patient with a good response to the topical lovastatin/cholesterol ointment - Kai Chen; Bin Hu; Qiang Chen; Fei Su; Liu-Qing Chen (Journal of Dermatological Treatment)
Background Congenital hemidysplasia with ichthyosiform nevus and limb defects (CHILD) syndrome is a rare X-linked dominant disorder characterized by a peculiar ichthyosiform nevus and limb defects. Linear porokeratosis (LP) is a distinct subtype of porokeratosis with hyperkeratotic nevus typically found on the extremities and linearly arranged along the lines of Blaschko. To our knowledge, the combination of CHILD syndrome and LP in a patient presenting inflammatory nevus on the limbs has never been reported.Patients and methods A fourteen-year-old Chinese girl presented with CHILD syndrome without limb abnormalities but with coexisting LP on her left leg and opisthenar. Clinical and laboratory examination, and Whole-Genome Sequencing (WGS) analysis of the NSDHL and PMVK gene were performed. The topical application of a compounded 2% lovastatin and 2% cholesterol ointment to skin lesions twice daily for up to 4 weeks, and treatment response was evaluated every week.Results Our patient presented with both of the clinical features of CHILD syndrome and LP. Further WGS revealed a genetic deletion in NSDHL (c.123delA, p.V42*) and a compound heterozygous mutation in the PMVK (c.88C > T, p.Q30*) gene, confirming the clinical diagnosis of our patient. Moreover, after 4 weeks of treatment, the skin lesion of the patient had displayed a good therapeutic response to the pathogenesis-directed therapy, and we didn’t observe any adverse events.Conclusions We report, for the first time in China, a case of a patient with both CHILD syndrome and LP with inflammatory nevi on the limbs. Furthermore, we provide evidence of the effectiveness of a topical lovastatin/cholesterol-based therapy for this patient.